The competences of leadership of senior students in Portugal - Bento, António (2009)
Pupils of secondary education develop during their schooling path diverse leadership abilities. However, this area of investigational study has attracted little attention on the part of Portuguese researchers. Thus, this research study intends to analyze the characteristics of leadership of the pupils of secondary education in two schools (one urban and another rural) of the Autonomous Region of Madeira (Portugal) and looks for to determine the existing differences concerning the type of school and the gender of the students in eight distinct domains: 1) self management; 2) interpersonal relations; 3) problem solving/decision making; 4) cognitive critical development/analysis; 5) organization and planning; 6) self-confidence; 7) diversity awareness; and, 8) technology. It was used, to collect data, the Student Leadership Outcomes Inventory (SLOI) (Vann, 2000) an instrument with 60 items which was constructed to measure the results of the experiences of leadership of the pupils in eight distinct areas. The respondents classify items in a Likert type scale with answers that vary between "I agree completely" to "I disagree completely". A total of 158 senior pupils participated in this study, proceeding from the student senior population of secondary education in the school year of 2008/2009 in one Mediterranean country (Portugal). The participants of this study had indicated moderate levels of abilities and techniques of leadership in the eight sub-scales; however, differences had been not found significant concerning the gender of the students, the age group and the type of school. In general, we can affirm that the Portuguese pupils finish secondary education with several characteristics and leadership abilities well developed.